2010
DOI: 10.1080/02699931.2010.516962
|View full text |Cite
|
Sign up to set email alerts
|

Cultural grounding of regret: Regret in self and interpersonal contexts

Abstract: The purpose of this study was to explore cultural similarities and differences in regret, focusing on distinctions between interpersonal and self-situations, and between action and inaction regrets. Japanese and American undergraduates were asked to describe regrets experienced in interpersonal and self-situations. We found that both situational and cultural contexts influenced the likelihood of regretting inactions over actions. Participants were more likely to recall inaction regrets in self-situations than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…Specifically, anticipation of regret can motivate individuals to behave in accord with their cultural norms (Komiya et al, 2011), meaning that regulation strategies could vary across cultures. Our study can only be read as illustrating the role of anticipated regret in the transition from latent to nascent entrepreneurship in Finland, and consequently, cross-cultural studies would be required to better understand the interplay of anticipated regret, cognition and behaviour in the broader entrepreneurship context.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Specifically, anticipation of regret can motivate individuals to behave in accord with their cultural norms (Komiya et al, 2011), meaning that regulation strategies could vary across cultures. Our study can only be read as illustrating the role of anticipated regret in the transition from latent to nascent entrepreneurship in Finland, and consequently, cross-cultural studies would be required to better understand the interplay of anticipated regret, cognition and behaviour in the broader entrepreneurship context.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Supporting this proposition, recent cultural comparisons (e.g., Chen et al, 2006;Komiya et al, 2011;Zou et al, 2009) have shown cultural differences with regard to regret between East Asia (e.g., Japan and China) and the United States. For example, Komiya et al (2011) found that Japanese students felt stronger regret than Americans in interpersonal situations, whereas no differences emerged with respect to the intensity of regrets experienced in situations involving only the self.…”
Section: Cultural Effects On the Content Of Regretmentioning
confidence: 59%
“…Supporting this proposition, recent cultural comparisons (e.g., Chen et al, 2006;Komiya et al, 2011;Zou et al, 2009) have shown cultural differences with regard to regret between East Asia (e.g., Japan and China) and the United States. For example, Komiya et al (2011) found that Japanese students felt stronger regret than Americans in interpersonal situations, whereas no differences emerged with respect to the intensity of regrets experienced in situations involving only the self. Moreover, Chen et al (2006) discussed the possibility that Chinese individuals were more likely than Americans to feel regret over acts of commission in school and family settings, reflecting their motivation to meet familial obligations (e.g., Heine & Lehman, 1997;Heine, Lehman, Markus, & Kitayama, 1999).…”
Section: Cultural Effects On the Content Of Regretmentioning
confidence: 59%
See 1 more Smart Citation
“…Robinson et al [52] have postulated that NA functions as a 'defense' mechanism by either provoking a passive state wherein watchfulness and reticence are prioritized or, alternatively, that individuals applying high levels of "assessment" invest more effort on ruminating prior to choice and these deliberations induce worry and other feelings linked to NA. Individuals identified through behavioral inaction tend to express more regret [53] and experience a higher degree of NA [54] through inaction than if they had attempted, even persisted, towards a goal [50,55]. Excessive hesitancy may accompany the pursuance of an "assessment" approach to choice and decision-making leading to inaction and reducing the quality of preferences and decisions [56].…”
Section: Discussionmentioning
confidence: 99%